Simulating and interpreting deep observations in the Hubble Ultra Deep Field with the JWST/NIRSpec low-resolution 'prism'. Issue 2 (6th September 2018) - Chevallard, Jacopo; Curtis-Lake, Emma; Charlot, Stéphane; Ferruit, Pierre; Giardino, Giovanna; Franx, Marijn; Maseda, Michael V; Amorin, Ricardo; Arribas, Santiago; Bunker, Andy; Carniani, Stefano; Husemann, Bernd; et al.
ABSTRACT: The James Webb Space Telescope ( JWST ) will enable the detection of optical emission lines in galaxies spanning a broad range of luminosities out to redshifts z ≳ 10. Measurements of key galaxy properties, such as star formation rate and metallicity, through these observations will provide unique insight into, e.g. the role of feedback from stars and active galactic nuclei (AGNs) in regulating galaxy evolution, the co-evolution of AGNs and host galaxies, the physical origin of the 'main sequence' of star-forming galaxies, and the contribution by star-forming galaxies to cosmic reionization. We present an original framework to simulate and analyse observations performed with the near-infrared spectrograph (NIRSpec) on board JWST . We use the beagle tool (BayEsian Analysis of GaLaxy sEds) to build a semi-empirical catalogue of galaxy spectra based on photometric spectral energy distributions of dropout galaxies in the Hubble Ultra Deep Field (HUDF). We demonstrate that the resulting catalogue of galaxy spectra satisfies different types of observational constraints on high-redshift galaxies, and use it as an input to simulate NIRSpec/prism ( R ∼ 100) observations. We show that a single 'deep' (∼100 ks) NIRSpec/prism pointing in the HUDF will enable S/N3 detections of multiple optical emission lines in ∼30 (∼60) galaxies at z ≳ 6 (z 4 - 6 ) down to m_F160W30 AB mag. Such observations will allow measurements of galaxy star formation rates, ionization parameters, and gas-phase metallicities within factors of 1.5, mass-to-light ratios within a factor of 2, galaxy ages within a factor of 3, and V -band attenuation optical depths with a precision of 0.3.